The maternal U1 haplogroup in the Koraga tribe as a correlate of their North Dravidian linguistic affinity - Sequeira, Jaison Jeevan; Vinuthalakshmi, Kadengodlu; Das, Ranajit; van Driem, George; Mustak, Mohammed S. (Frontiers in Genetics, 2024)
Introduction: The Koraga tribe are an isolated endogamous tribal group found in the southwest coastal region of India. The Koraga language shares inherited grammatical features with North Dravidian languages. To seek a possible genetic basis for this exceptionality and understand the maternal lineage pattern, we have aimed to reconstruct the inter-population and intra-population relationships of the Koraga tribal population by using mtDNA markers for the hypervariable regions along with a partial coding region sequence analysis. Methods and Results: Amongst the 96 individuals studied, we observe 11 haplogroups, of which a few are shared and others are unique to the clans Soppu, Oṇṭi and Kuṇṭu. In addition to several deep rooted Indian-specific lineages of macrohaplogroups M and U, we observe a high frequency of the U1 lineage (∼38%), unique to the Koraga. A Bayesian analysis of the U1 clade shows that the Koraga tribe share their maternal lineage with ancestral populations of the Caucasus at the cusp of the Last Glacial Maximum. Discussion: Our study suggests that the U1 lineage found in the Indian subcontinent represents a remnant of a post-glacial dispersal. The presence of West Asian U1 when viewed along with historical linguistics leads us to hypothesise that Koraga represents a mother tongue retained by a vanquished population group that fled southward at the demise of the Indus civilisation as opposed to a father tongue, associated with a particular paternal lineage.